2018
DOI: 10.1080/1745039x.2018.1492806
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding diets containing essential oils and betaine to heat-stressed growing-finishing pigs

Abstract: This study was to evaluate the effects of dietary essential oils (EO) and betaine on growth performance, nutrient digestibility and serum hormones in growing-finishing pigs under heat stress conditions. A total of 96 crossed pigs [(Landrace × Yorkshire) × Duroc] with an initial body weight (BW) of 24.7 ± 0.27 kg were used in an 18-week trial. Pigs were randomly allocated to four treatments according to BW and gender. There were six replication pens in each treatment, with four pigs (two barrows and two gilts) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…However, betaine also plays a role in the methionine cycle, where it acts as a substrate for the enzyme betaine homocysteine S-methyltransferase (BHMT), a back-up to methionine synthase, which converts homocysteine back to methionine (Perez-Miguelsanz et al, 2017). Betaine has already proven beneficial in heat stress for its ability to restore growth rates in heat-stressed animals (Mendoza et al, 2017;Lan and Kim, 2018). There is also evidence that betaine supplementation improves lactation, as well as restoring follicle diameter and shortening ovulation time in heat-stressed sows (Cabezón et al, 2017).…”
Section: Cow Feeding During Heat Stress: What and Whenmentioning
confidence: 99%
“…However, betaine also plays a role in the methionine cycle, where it acts as a substrate for the enzyme betaine homocysteine S-methyltransferase (BHMT), a back-up to methionine synthase, which converts homocysteine back to methionine (Perez-Miguelsanz et al, 2017). Betaine has already proven beneficial in heat stress for its ability to restore growth rates in heat-stressed animals (Mendoza et al, 2017;Lan and Kim, 2018). There is also evidence that betaine supplementation improves lactation, as well as restoring follicle diameter and shortening ovulation time in heat-stressed sows (Cabezón et al, 2017).…”
Section: Cow Feeding During Heat Stress: What and Whenmentioning
confidence: 99%
“…Some researchers find that betaine has osmotic protection properties that help protecting the proteins and enzymes of intestinal cells from environmental stress. Inclusion of betaine in the diet have a beneficial effect on relieving physical reactions to heat stress in both poultry and growing-finishing pigs [10,11]. However, the specific mechanisms regarding how does it improve the intestinal function remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The increased ROS resulted in stimulated intracellular and extracellular superoxide formation and was responsible for oxidative stress [15]. Heat stress generates ROS, which may modulate the inflammatory transcription factor nuclear factor-κB [16], inducing hormonal and metabolic changes, secretion of inflammatory cytokines [17], and decrease the level of antioxidant enzymes [17]. Former studies demonstrated that the pro-inflammatory cytokines level will increase under heat stress [13,14,18].…”
Section: Introductionmentioning
confidence: 99%